Mobile application to promote environmental awareness - Nur Tatiana Azman (Nanyang Technological University, 2020)
Climate change has been a pressing issue for many years, and this has been observable especially in Singapore. The first step in mitigating the effects of climate change is to pick up a recycling habit. However, some Singaporeans do not consciously recycle and some still lack the knowledge when it comes to the types of items that can or cannot be recycled. The objective of this project was to develop an app that educates users about recycling and to encourage them to develop a recycling habit. An Android app was developed using Android Studio with four main features – Info, Tracker, Feed and Location, and positive functionality test results were produced.